Penantian dalam Iman Kristen: Suatu Kajian Biblika-Teologis tentang Ketekunan, Pengharapan, dan Pengenalan akan Allah - Rasmalem Raya Sembiring; Robbye Manik; Aslinawati; Petrus Posma Silaban (Sekolah Tinggi Teologi Sola Gratia Medan, 2026)
Abstract Waiting is an integral part of Christian faith, although modern culture often views it negatively as a sign of delay or God’s absence. This article examines waiting as part of God’s providential work in redemptive history through a biblical-theological and redemptive-historical approach, enriched by systematic theological reflection. The study demonstrates that waiting is used by God to cultivate perseverance in faith and deepen believers’ knowledge of Christ. Christian waiting is not passive resignation, but a spirituality of hope rooted in God’s promises and lived within the eschatological tension of the “already” and the “not yet.” Furthermore, waiting possesses christological, eschatological, relational, and ecclesiological dimensions because the biblical pattern of waiting finds its fulfillment in Christ and shapes the church as a community of hope awaiting the fullness of God’s kingdom. Thus, waiting should be understood not as a sign of God’s absence, but as a theological space in which God purifies faith, forms perseverance, and draws His people into a deeper knowledge of Himself. Keywords: waiting, perseverance, knowledge of God, providence, redemptive history Abstrak Penantian merupakan bagian penting dalam kehidupan iman Kristen, meskipun budaya modern sering memandangnya secara negatif sebagai tanda keterlambatan atau ketidakhadiran Allah. Artikel ini mengkaji penantian sebagai bagian dari karya providensial Allah dalam sejarah penebusan dengan pendekatan teologi biblika dan redemptive-historical, serta refleksi teologi sistematika. Hasil penelitian menunjukkan bahwa penantian dipakai Allah untuk membentuk ketekunan iman dan memperdalam pengenalan umat percaya kepada Kristus. Penantian Kristen bukan sikap pasif, melainkan spiritualitas pengharapan yang berakar pada janji Allah dan hidup dalam ketegangan antara “sudah” dan “belum.” Selain itu, penantian memiliki dimensi kristologis, eskatologis, relasional, dan eklesiologis karena seluruh pola penantian Alkitab digenapi dalam Kristus dan membentuk gereja sebagai komunitas pengharapan akan kerajaan Allah. Dengan demikian, penantian dipahami sebagai ruang teologis tempat Allah memurnikan iman, membentuk ketekunan, dan membawa umat-Nya semakin mengenal diri-Nya. Kata Kunci: penantian, ketekunan, pengenalan akan Allah, providensia, sejarah penebusan.